2016
DOI: 10.1007/s00248-016-0862-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylotype Dynamics of Bacterial P Utilization Genes in Microbialites and Bacterioplankton of a Monomictic Endorheic Lake

Abstract: Microbes can modulate ecosystem function since they harbor a vast genetic potential for biogeochemical cycling. The spatial and temporal dynamics of this genetic diversity should be acknowledged to establish a link between ecosystem function and community structure. In this study, we analyzed the genetic diversity of bacterial phosphorus utilization genes in two microbial assemblages, microbialites and bacterioplankton of Lake Alchichica, a semiclosed (i.e., endorheic) system with marked seasonality that varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…These overrepresented genes were hypothesized to play an important role in controlling carbonate precipitation through the production of stored polyphosphate, which chelates metals, such as calcium (Breitbart et al, 2009;Valdespino-Castillo et al, 2014). However, phylotyping of alkaline phosphatase genes in microbialites from Lake Alchichica suggested that Alphaproteobacteria were the possible hosts of these genes (Valdespino-Castillo et al, 2017), in contrast to the cyanobacterial Rivularia spp. as shown here.…”
Section: Resultsmentioning
confidence: 99%
“…These overrepresented genes were hypothesized to play an important role in controlling carbonate precipitation through the production of stored polyphosphate, which chelates metals, such as calcium (Breitbart et al, 2009;Valdespino-Castillo et al, 2014). However, phylotyping of alkaline phosphatase genes in microbialites from Lake Alchichica suggested that Alphaproteobacteria were the possible hosts of these genes (Valdespino-Castillo et al, 2017), in contrast to the cyanobacterial Rivularia spp. as shown here.…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding this N relief, the diazotrophic activity of microbialites is detected before, during and after the bloom. It might be possible that other pathways of the N cycle, such as nitrification, anam-mox and denitrification, also exhibit seasonal varia-tions, changing N-cycling genetic diversity in time (as was described for P utilization genes in micro-bialites and bacterioplankton within the system, see Valdespino-Castillo et al 2016). However, further studies must be done to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…A metagenomic exploration over two locations of Cuatro Ciénegas Basin (same pond of our PAI microbialite) showed microbialites were enriched in genes for phosphorus metabolism, establishment and development of biofilms and heterotrophic respiration (Breitbart et al, 2009 ). A vast genetic diversity for nitrogen (N) and phosphorus (P) cycling has been described for the microbialites from Alchichica soda lake (Beltrán et al, 2012 ; Valdespino-Castillo et al, 2014 , 2017 ; Alcántara-Hernández et al, 2017 ), where microbialites actively fix nitrogen (Beltrán et al, 2012 ). The geochemical characteristics (major cations) of microbialite ambient waters (Table 1 ) were compiled from different reference studies.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have found that microbialites harbor a highly diverse microbial community fundamentally driven by environmental factors such as pH, conductivity and availability of nitrate (Centeno et al, 2012 ). Genomic surveys for some microbialites have revealed a broad potential for photoautotrophy and heterotrophic pathways involved in biogeochemical C, S, N, and P cycling (Beltrán et al, 2012 ; Valdespino-Castillo et al, 2014 , 2017 ; Cerqueda-García and Falcón, 2016 ; Saghaï et al, 2016 ; Alcántara-Hernández et al, 2017 ); and synthesis of enzyme cofactors, amino acids, production and degradation of extracellular polymeric substances (EPS) (Breitbart et al, 2009 ; Myshrall et al, 2010 ; Mobberley et al, 2013 ; White et al, 2015 ; Cerqueda-García and Falcón, 2016 ). Microbialite extracellular polymeric substances provide an adequate environment for binding transition metals to organic ligands (Geesey et al, 1988 ; Sforna et al, 2017 ) that may be microbe-dependent (Micheletti et al, 2008 ) and needs further exploration.…”
Section: Introductionmentioning
confidence: 99%